1990
DOI: 10.1037/1040-3590.2.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting low scores on the WISC—R Third Factor: It's more than distractibility.

Abstract: The Wechsler Intelligence Scale for Children-Revised consists of three factors: Perceptual Organization, Verbal Comprehension, and the Third Factor, also called Freedom from Distractibility. Children referred for learning and behavioral problems frequently obtain low Third Factor scores. Although resistance to the effects of distracting stimuli may be necessary for optimum performance on the Third Factor, many other hypotheses may account for low scores. This article reviews studies that elucidate the meaning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 59 publications
1
25
0
2
Order By: Relevance
“…The few relationships that were observed would therefore not withstand strict corrections for multiple comparisons, and should be interpreted with great caution. However, there is a slight hint that prenatal substance exposure may exert an effect on distractibility, or in Wielkiewicz's (1990) terms "executive" and short term memory processes involved in planning, monitoring and evaluating task performance, via the right lateral orbitofrontal cortex. This is only one possibility, but one that is theoretically meaningful.…”
Section: Functional Significance Of Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The few relationships that were observed would therefore not withstand strict corrections for multiple comparisons, and should be interpreted with great caution. However, there is a slight hint that prenatal substance exposure may exert an effect on distractibility, or in Wielkiewicz's (1990) terms "executive" and short term memory processes involved in planning, monitoring and evaluating task performance, via the right lateral orbitofrontal cortex. This is only one possibility, but one that is theoretically meaningful.…”
Section: Functional Significance Of Effectsmentioning
confidence: 99%
“…While total IQ is calculated from all subtests, the Freedom from distractibility factor is comprised of the Arithmetic, Digit Span and Coding subtests. It has been suggested that in addition to resistance to the effects of distracting stimuli, this factor reflects executive and short term memory processes involved in planning, monitoring and evaluating task performance (Wielkiewicz, 1990). The Child Behavior Check List (CBCL; Achenbach, 1991) was also administered to all children's families at the time of administration of WISC-R.…”
Section: Behavioral Datamentioning
confidence: 99%
“…24 All subjects' FA data were aligned into a common space by using nonlinear registration. [29][30][31] Every participant was registered to every other participant, and the most typical was chosen as the target (ie, the target image that minimized the amount of warping required for all other subjects to align to it).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Moreover, the FD profile was significantly lower than the childrens' full scale IQ (FSIQ) for the ADHD sample. Additional research with groups of children with and without ADHD found that, on average, scores of the ADHD groups on those two subtests were significantly lower than the scores for non-ADHD groups (Anastopoulos, Spisto, & Maher, 1994;Wielkiewicz, 1990).…”
Section: Introductionmentioning
confidence: 99%